Penggunaan Kriptografi Dalam Novel Digital Fortress (Benteng Digital) Karya dan Brown - Farid Rieziq; Difa Pradana Prihantoro; Eva Dwi Kurniawan (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
Cryptography has become a technology that has developed rapidly in the last decade. The development of this technology is changing the paradigm for information security in maintaining the confidentiality and integrity of data. The aim of this research is to see how cryptographic technology is used in the novel Digital Fortress. The method used uses a hermeneutic approach. The results obtained show that the use of cryptography in this literary work is realized through a decryption machine called Transltr which has a unique ability to break codes. The use of cryptography in this novel is also described as a tool to protect or threaten information security, depending on who is using it and for what purpose.